2019
DOI: 10.1515/gps-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera leaf extract mediated green synthesis of selenium nanoparticles and assessment of their In vitro antimicrobial activity against spoilage fungi and pathogenic bacteria strains

Abstract: Selenium as an essential trace element for the health of the humans was used to hydrothermally synthesis of selenium nanoparticle (Se NPs) using Aloe vera leaf extract (ALE). Effects of synthesis parameters namely; amount of ALE (1–5 ml) and amount of Na2SeO3 solution (10–30 ml), on the particle size and colour intensity of the solution containing Se NPs were studied using response surface methodology. FT-IR spectroscopy, UV-Vis spectrophotometry, DLS analyzer and TEM were used to determine the specifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(99 citation statements)
references
References 27 publications
2
95
0
2
Order By: Relevance
“…Regarding biogenic synthesized Se-NPs, the antimicrobial activities of NPs were documented and confirmed; Aloe vera-synthesized Se-NPs were able to inhibit two species (S. aureus and E. coli), with larger ZOI around S. aureus [12]. Former investigations also indicated the bactericidal influences of the biosynthesized Se-NPs against both mentioned bacterial strains, but with varied potentialities [36,37].…”
Section: Antibacterial Activity Of Npsmentioning
confidence: 91%
See 1 more Smart Citation
“…Regarding biogenic synthesized Se-NPs, the antimicrobial activities of NPs were documented and confirmed; Aloe vera-synthesized Se-NPs were able to inhibit two species (S. aureus and E. coli), with larger ZOI around S. aureus [12]. Former investigations also indicated the bactericidal influences of the biosynthesized Se-NPs against both mentioned bacterial strains, but with varied potentialities [36,37].…”
Section: Antibacterial Activity Of Npsmentioning
confidence: 91%
“…Selenium nanoparticles (Se-NPs) were evidenced to possess extra bioactivities and functionalities as potent antioxidant, antibacterial, antifungal and anticancer agents [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Small P-values (P < 0.05) were considered as statistically significant [18]. Surface and contour plots were also utilized to better visualize the influences of the synthesized factors on the response factors [19,20]. Graphical and numerical optimizations were applied to predict optimal area and exact values of independent variables to fabricate ZnO NPs with maximum antioxidant and antibacterial activities.…”
Section: Experimental Design and Data Statistical Analysismentioning
confidence: 99%
“…Numerous nanoparticles have been formulated using different physical, chemical, and green nanoparticle synthesis techniques. Among all of these, green synthesis methods are known to be the most economical and environmental friendly technique owing to the use of natural compounds in the development of nanoparticles [9]. Various studies have shown the use of different plant extracts for the formulation of AgNPs.…”
Section: Introductionmentioning
confidence: 99%